2018
DOI: 10.1161/jaha.117.008175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wave Reflection and Arterial Stiffness on the Risk of Development of Hypertension in Japanese Men

Abstract: BackgroundWe conducted analyses of repeated‐measures data to examine whether pressure wave reflection acts additively or synergistically with arterial stiffness in the pathogenesis of hypertension.Methods and ResultsIn 3172 middle‐aged (42±9 years) healthy Japanese men without hypertension at the study baseline, systolic and diastolic blood pressures, brachial–ankle pulse wave velocity, and radial augmentation index were measured annually during a 9‐year study period. Of these, 474 participants (15%) developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…End of the study period was defined by the last examination of the participants who had undergone at least 2 annual examinations. 8,9 Among the whole study subjects included, 474 (14.5%) developed hypertension (of which 152 were already receiving antihypertensive medication by the end of the study period) by the end of the study period. The mean number of times that the variables were measured was 5.2±2.1×, and the mean duration of follow-up was 6.4±2.5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…End of the study period was defined by the last examination of the participants who had undergone at least 2 annual examinations. 8,9 Among the whole study subjects included, 474 (14.5%) developed hypertension (of which 152 were already receiving antihypertensive medication by the end of the study period) by the end of the study period. The mean number of times that the variables were measured was 5.2±2.1×, and the mean duration of follow-up was 6.4±2.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The cohort consisted of employees working at the headquarters of a single large Japanese construction company located in downtown Tokyo. According to the Occupational Health and Safety Law in Japan, it is mandatory for all company employees to undergo annual health checkups.…”
Section: Design and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for arterial stiffness, it is one of the earliest recognized markers of hypertension and plays an important role in the development and prognosis of hypertension. It is reported that arterial stiffness makes an important contribution to the increase in systolic blood pressure (SBP) and the development of hypertension in general population, independently of traditional hypertension risk factors [9][10][11][12][13][14][15]. Besides, changes in both small and large arteries could predict future hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, because of its reproducibility and simplicity [6, 7], brachia–ankle pulse wave velocity (baPWV) is a widely used method for assessing arterial stiffness in studies of large sample sizes [7]. baPWV was found to be related to increased risk of stroke [8], total cardiovascular events and all-cause mortality [9], and was shown to positively associated with hypertension [10] and the presence of coronary calcium [11] or left ventricular mass [12]. Nevertheless, there are limited studies on baPWV and diabetes.…”
Section: Introductionmentioning
confidence: 99%